Cells and Batteries
By using diaphragm coating layers with different adhesive formulations in the inner and outer layers of the battery cell, the problem of deviation of the bonding strength between the pole sheet and the diaphragm in the thickness direction of the battery cell is solved, and the cell hardness and energy density are improved.
Patent Information
- Application Number
- CN202411854285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-17
AI Technical Summary
There is a deviation in the bonding strength between the pole sheet and the diaphragm in the thickness direction of the existing battery cells, which affects the hardness and energy density of the battery cells.
The inner and outer layers of the battery cell are respectively used to coat the diaphragm with different adhesive formulations. By adjusting the proportion and types of B1 and B2 adhesives, the bonding forces between the inner and outer layers are balanced.
The uniform bond between the inner and outer layers of the battery cell and the electrode sheet is achieved, the hardness and energy density of the battery cell are improved, and the huge gap in internal stress and adhesion during the production process is reduced.
Smart Images

Figure CN119381702B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to battery cells and batteries. Background Art
[0002] In order to improve the energy density of the battery cell, the size of the battery cell is getting bigger and bigger, and the thickness of the battery cell is getting thicker and thicker. Relatively speaking, when the glue-coated diaphragm is hot pressed (when the battery cell is hot pressed, the glue coating on the diaphragm on the outer layer of the battery cell is heated first, and under the action of pressure, the electrode is more likely to bond with the glue coating on the diaphragm, while the temperature of the diaphragm coating on the inner layer of the battery cell is relatively lower, and the coating and the electrode are relatively poorer), so the thick battery cell has a deviation in the bonding strength between the inner electrode and the diaphragm, which affects the hardness of the battery cell.
[0003] The current glue coating formula of the glue-coated diaphragm is the same, which means that in order to ensure a good bonding effect between the electrode and the glue-coated diaphragm, the bonding strength between the inner diaphragm and the electrode is mainly improved by increasing the hot pressing temperature and extending the hot pressing time. Summary of the invention
[0004] In view of this, the present invention provides a battery cell and a battery. In the battery cell, the diaphragm adhesive layers corresponding to the inner layer area and the outer layer area adopt different adhesive formulations, so as to balance the bonding effect of the diaphragm and the pole piece inside the entire core package and the production efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner region 100 and a battery cell outer region 200 from the center to the edge of the battery cell;
[0007] The battery cell includes a diaphragm 30 and a pole piece. The diaphragm 30 includes a first diaphragm 31 and a second diaphragm 32. The first diaphragm 31 is arranged in the inner layer area 100 of the battery cell, and the second diaphragm 32 is arranged in the outer layer area 200 of the battery cell.
[0008] The first diaphragm 31 includes a first adhesive layer 313, and the first adhesive layer 313 includes a first adhesive;
[0009] The second diaphragm 32 includes a second adhesive layer 323, and the second adhesive layer 323 includes a second adhesive;
[0010] The bonding force between the first diaphragm and the electrode is recorded as A1, and the bonding force between the second diaphragm and the electrode is recorded as A2. A1 and A2 satisfy the following relationship:
[0011] -3≤A1-A2≤0.
[0012] Preferably, the bonding force between the first diaphragm and the electrode piece is 7 to 10 N / m.
[0013] Preferably, the bonding force between the second diaphragm and the electrode piece is 9 to 11 N / m.
[0014] In an embodiment of the present invention, the first adhesive includes a B1 adhesive and a C adhesive, and the second adhesive includes a B2 adhesive and a C adhesive; and the mass percentage of the B1 adhesive in the first adhesive is greater than or equal to the mass percentage of the B2 adhesive in the second adhesive.
[0015] In an embodiment of the present invention, the B1 type binder includes at least one of acrylic acid-modified PVDF, hydroxyl-modified PVDF, and polycarboxylic acid-modified PVDF.
[0016] In an embodiment of the present invention, the B2 type binder includes at least one of tetrafluoroethylene-modified PVDF, hexafluoroethylene-modified PVDF, and trifluoroethylene-modified PVDF.
[0017] In an embodiment of the present invention, the type C binder includes at least one of acrylonitrile-modified acrylate, acrylamide-modified acrylate, acrylonitrile-modified butyl acrylate, and acrylonitrile-acrylic acid-acrylic acid terpolymer.
[0018] Preferably, the first adhesive comprises, by weight: 0.1 to 20 parts of a B1 type adhesive and 1 to 20 parts of a C type adhesive.
[0019] Preferably, the second adhesive comprises, by weight: 0.1 to 20 parts of a B2 type adhesive and 1 to 20 parts of a C type adhesive.
[0020] Preferably, the first diaphragm 31 further includes a first ceramic layer 312 , and the first ceramic layer 312 is disposed between the first base film 311 and the first adhesive layer 313 of the first diaphragm 31 .
[0021] Preferably, the second diaphragm 32 further includes a second ceramic layer 322 , and the second ceramic layer 322 is disposed between the second base film 321 and the second adhesive layer 323 of the second diaphragm 32 .
[0022] In the embodiment of the present invention, the first ceramic layer includes first ceramic particles, the second ceramic layer includes second ceramic particles, and the particle size D of the first ceramic particles is 50 Greater than or equal to the particle size D of the second ceramic particles 50 .
[0023] Preferably, the particle size D of the first ceramic particles is 50 0.8~1.2μm.
[0024] Preferably, the particle size D of the second ceramic particles is 50 It is 0.4~0.8μm.
[0025] In an embodiment of the present invention, the first ceramic layer includes, by weight: 80 to 98 parts of first ceramic particles, 1 to 20 parts of a third binder, 0.1 to 1 part of a first thickener, and 0.1 to 1 part of a first wetting agent.
[0026] In an embodiment of the present invention, the second ceramic layer includes, by mass, 80 to 98 parts of second ceramic particles, 1 to 20 parts of a fourth binder, 0.1 to 1 part of a second thickener, and 0.1 to 1 part of a second wetting agent.
[0027] Preferably, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell.
[0028] In an embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell.
[0029] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. In the present invention, the first adhesive layer in the first diaphragm disposed in the inner region of the battery core includes a first adhesive, and the second adhesive layer in the second diaphragm disposed in the outer region of the battery core includes a second adhesive, the first adhesive includes a B1 adhesive and a C adhesive; the second adhesive includes a B2 adhesive and a C adhesive, and the mass percentage of the B1 adhesive in the first adhesive is greater than or equal to the mass percentage of the B2 adhesive in the second adhesive. Among them, the B1 adhesive in the first adhesive has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chain in the pole piece, improving the bonding force, corresponding to the first diaphragm with better flexibility, and it is easier to anchor and bond the first diaphragm with the pole piece during hot pressing; while the B2 adhesive has a smaller bonding force, and the second diaphragm has a smaller flexibility deviation, and its temperature rises faster during hot pressing, making it easier to bond the pole piece with the second diaphragm, and the second diaphragm can also meet the bonding effect between the diaphragm and the pole piece in the outer region of the battery core. Therefore, the present invention can ultimately achieve the purpose of comprehensive production efficiency, balancing the bonding effect of the diaphragm inside the entire core package and the pole piece as well as production efficiency.
[0032] 2. In the prior art, the coating layer formula of the coated diaphragm is the same, and there is a problem of relative deviation in wettability between the inner diaphragm and the electrode of the battery core. In the preferred embodiment of the present invention, the first diaphragm further includes a first ceramic layer, the second diaphragm includes a second ceramic layer, and the particle size D of the first ceramic particles in the first ceramic layer is 50 Greater than the particle size D of the second ceramic particles in the second ceramic layer 50. The first ceramic layer of the first diaphragm has larger pores between ceramic particles due to the addition of larger ceramic particles, which is more conducive to electrolyte infiltration; the second ceramic layer of the second diaphragm uses ceramic particles with smaller particles. Although the electrolyte wettability is relatively poor, it can meet the electrolyte wettability requirements of the diaphragm in the outer layer of the battery cell. Therefore, this preferred solution can simultaneously solve the problems of diaphragm wettability deviation and adhesion deviation in the inner layer of the battery cell, which is conducive to achieving a better comprehensive effect of adhesion and wettability of the entire battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is the division of the inner and outer areas of the wound battery cell.
[0034] Figure 2 It is the division of the inner and outer areas in the laminated battery cell.
[0035] Figure 3 This is a schematic diagram of the structure of the unwound diaphragm of Example 1 of the present invention.
[0036] Figure 4 It is a schematic diagram of the structure of the wound battery cell of the present invention.
[0037] The reference numerals are as follows:
[0038] 100: inner area of the battery cell;
[0039] 200: outer area of the battery cell;
[0040] 300: vertical center axis;
[0041] 10: Negative electrode
[0042] 20: positive electrode;
[0043] 30: diaphragm;
[0044] 31: first diaphragm;
[0045] 311: first basement membrane;
[0046] 312: first ceramic layer;
[0047] 313: first adhesive coating layer;
[0048] 314: first binder particles;
[0049] 32: second diaphragm;
[0050] 321: Second basement membrane;
[0051] 322: second ceramic layer;
[0052] 323: second adhesive coating layer;
[0053] 324: Second binder particles. DETAILED DESCRIPTION
[0054] The present invention discloses a cell and a battery, and those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0055] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0056] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0057] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0060] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0061] Specifically, the present invention adopts the following technical solutions:
[0062] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner layer region 100 and a battery cell outer layer region 200 from the center to the edge of the battery cell;
[0063] The battery cell includes a diaphragm 30 and a pole piece. The diaphragm 30 includes a first diaphragm 31 and a second diaphragm 32. The first diaphragm 31 is arranged in the inner layer area 100 of the battery cell, and the second diaphragm 32 is arranged in the outer layer area 200 of the battery cell.
[0064] The first diaphragm 31 includes a first adhesive layer 313, and the first adhesive layer 313 includes a first adhesive;
[0065] The second diaphragm 32 includes a second adhesive layer 323, and the second adhesive layer 323 includes a second adhesive;
[0066] The bonding force between the first diaphragm and the electrode is recorded as A1, and the bonding force between the second diaphragm and the electrode is recorded as A2. A1 and A2 satisfy the following relationship:
[0067] -3≤A1-A2≤0.
[0068] In an embodiment of the present invention, Figure 1 and Figure 2 As shown, the inner region 100 of the battery core refers to the region close to the vertical center axis 300 of the battery core, and the outer region 200 of the battery core refers to the region away from the vertical center axis 300 of the battery core. For example, the battery core is a wound battery core, such as Figure 1 As shown, the inner region 100 of the battery cell refers to the region closer to the vertical center axis 300 in the multilayer structure of the winding structure after the pole piece is wound along the vertical center axis 300 to form a winding structure, and accounts for 10% to 75% of the overall thickness of the battery cell (denoted as H). The outer region 200 of the battery cell refers to the region farther from the vertical center axis 300 of the winding structure, and accounts for 25% to 90% of the overall thickness of the battery cell. For example, the battery cell is a laminated battery cell, such as Figure 2 As shown, the inner region 100 of the battery cell refers to the region closer to the vertical center axis 300 in the multilayer structure of the stacked structure after the pole pieces are stacked along the vertical center axis 300 to form a stacked structure, and occupies 10% to 75% of the overall thickness of the battery cell (denoted as H). The outer region 200 of the battery cell refers to the region farther from the vertical center axis 300 of the stacked structure, and occupies 25% to 90% of the overall thickness of the battery cell.
[0069] In the prior art, the adhesion between the diaphragm in the inner layer area of the battery cell and the pole piece is poor, and the adhesion between the diaphragm in the outer layer area of the battery cell and the pole piece is relatively large, resulting in a large disparity in adhesion across the entire thickness and relatively high internal stress. In the present invention, the first diaphragm disposed in the inner layer area of the battery cell includes a first adhesive, and the second diaphragm disposed in the outer layer area of the battery cell includes a second adhesive. Among them, the first adhesive has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chain in the pole piece, improving the adhesion, and the corresponding diaphragm has better flexibility, and is easier to anchor and bond with the pole piece during hot pressing, thereby reducing the DC internal resistance of the battery, which is beneficial to improving the cycle performance of the battery; the second adhesive has a smaller adhesion, and the adhesive makes the diaphragm heat up faster during hot pressing, making it easier to bond with the pole piece.
[0070] In an embodiment of the present invention, the value of A1-A2 is -3 to 0. Exemplarily, the value of A1-A2 is any value among -3, -2.5, -2.2, -2, -1.7, -1.5, -1.1, -1, -0.8, -0.5, 0 or any value within the range of any two of the above values.
[0071] Preferably, the bonding strength between the first diaphragm and the pole piece is 7 to 10 N / m. Exemplarily, the bonding strength between the first diaphragm and the pole piece is any value among 7 N / m, 7.5 N / m, 8 N / m, 8.5 N / m, 9 N / m, 9.5 N / m, 10 N / m, or any value within the range of any two of the above values.
[0072] Preferably, the bonding strength between the second diaphragm and the electrode piece is 9-11 N / m. Exemplarily, the bonding strength between the second diaphragm and the electrode piece is any value among 9 N / m, 9.5 N / m, 10 N / m, 10.5 N / m, 11 N / m, or any value within the range of any two of the above values.
[0073] In an embodiment of the present invention, the first adhesive includes a B1 adhesive and a C adhesive, and the second adhesive includes a B2 adhesive and a C adhesive; and the mass percentage of the B1 adhesive in the first adhesive is greater than or equal to the mass percentage of the B2 adhesive in the second adhesive.
[0074] In an embodiment of the present invention, the B1 type binder includes at least one of acrylic acid modified PVDF, hydroxyl modified PVDF, and polycarboxylic acid modified PVDF. The B1 type binder has more polar functional groups, which is conducive to forming a stronger hydrogen bond interaction with the binder molecules of the pole piece, thereby improving the bonding force between the diaphragm and the pole piece.
[0075] In an embodiment of the present invention, the B2 type binder includes at least one of tetrafluoroethylene-modified PVDF, hexafluoroethylene-modified PVDF, and trifluoroethylene-modified PVDF.
[0076] In an embodiment of the present invention, the type C binder includes at least one of acrylonitrile-modified acrylate, acrylamide-modified acrylate, acrylonitrile-modified butyl acrylate, and acrylonitrile-acrylic acid-acrylic acid terpolymer.
[0077] Preferably, in parts by mass, the first binder includes 0.1 to 20 parts of a B1 binder and 1 to 20 parts of a C binder. Exemplarily, the first binder includes 9 parts of a B1 binder and 1 part of a C binder; or the first binder includes 0.1 parts of a B1 binder and 10 parts of a C binder; or the first binder includes 0.1 parts of a B1 binder and 20 parts of a C binder; or the first binder includes 20 parts of a B1 binder and 1 part of a C binder; or the first binder includes 0.1 parts of a B1 binder and 1 part of a C binder; or the first binder includes 5 parts of a B1 binder and 5 parts of a C binder; or the first binder includes 10 parts of a B1 binder and 5 parts of a C binder.
[0078] Preferably, the second binder includes 0.1 to 20 parts of a B2 binder and 1 to 20 parts of a C binder, by weight. Exemplarily, the second binder includes 9 parts of a B2 binder and 1 part of a C binder; or the second binder includes 0.1 parts of a B2 binder and 20 parts of a C binder; or the second binder includes 20 parts of a B2 binder and 1 part of a C binder; or the second binder includes 0.1 parts of a B2 binder and 1 part of a C binder; or the second binder includes 5 parts of a B2 binder and 5 parts of a C binder; or the second binder includes 10 parts of a B2 binder and 5 parts of a C binder.
[0079] In an embodiment of the present invention, the electrode sheet includes a positive electrode sheet and a negative electrode sheet.
[0080] In an embodiment of the present invention, the first coating layer is disposed on at least one side surface of the first base film of the first diaphragm, and the second coating layer is disposed on at least one side surface of the second base film of the second diaphragm.
[0081] In a specific embodiment of the present invention, the first adhesive layer is disposed on one side surface of the first base film, and the second adhesive layer is disposed on one side surface of the second base film.
[0082] In an embodiment of the present invention, when the first coating layer is arranged on one side surface of the first base film and the second coating layer is arranged on one side surface of the second base film, preferably the first coating layer and the second coating layer are in contact with the positive electrode sheet, the adhesion force between the first diaphragm and the positive electrode sheet is recorded as A1, and the adhesion force between the second diaphragm and the positive electrode sheet is recorded as A2.
[0083] More preferably, the first diaphragm 31 further includes a first ceramic layer 312 , and the first ceramic layer 312 is disposed between the first base film 311 and the first adhesive layer 313 .
[0084] More preferably, the second diaphragm 32 further includes a second ceramic layer 322 , and the second ceramic layer 322 is disposed between the second base film 321 and the second adhesive layer 323 .
[0085] The ceramic layer can increase the thermal stability and mechanical strength of the base film, making the battery excellent in high temperature resistance and puncture resistance, while not affecting the permeability of the diaphragm, ensuring the flow of lithium ions, thereby improving safety. In addition, the pores of the ceramic layer are larger than those of the base film, which can increase the wettability and liquid retention of the diaphragm.
[0086] In an embodiment of the present invention, the first ceramic layer includes first ceramic particles, and the second ceramic layer includes second ceramic particles.
[0087] Preferably, the particle size D of the first ceramic particles is 50 Greater than or equal to the particle size D of the second ceramic particles 50 .
[0088] More preferably, the particle size D of the first ceramic particles is 50 Greater than the particle size D of the second ceramic particles 50 .
[0089] Preferably, the particle size D of the first ceramic particles is 50 For example, the particle size D of the first ceramic particles is 0.8 to 1.2 μm. 50 It is any value among 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, or any value within the range consisting of any two of the above values.
[0090] Preferably, the particle size D of the second ceramic particles is 50 For example, the particle size D of the first ceramic particles is 0.4 to 0.8 μm. 50 It is any value among 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm or any value within the range consisting of any two of the above values.
[0091] In an embodiment of the present invention, the first ceramic layer includes, by mass, 80 to 98 parts of first ceramic particles, 1 to 20 parts of the third binder, 0.1 to 1 part of the first thickener, and 0.1 to 1 part of the first wetting agent. Exemplarily, the first ceramic layer includes: 95.4 parts of the first ceramic particles, 4 parts of the third binder, 0.4 parts of the first thickener, and 0.2 parts of the first wetting agent.
[0092] In an embodiment of the present invention, the second ceramic layer includes, by mass, 80 to 98 parts of second ceramic particles, 1 to 20 parts of a fourth binder, 0.1 to 1 part of a second thickener, and 0.1 to 1 part of a second wetting agent. Exemplarily, 94.4 parts of second ceramic particles, 5 parts of a fourth binder, 0.4 parts of a second thickener, and 0.2 parts of a second wetting agent.
[0093] In an embodiment of the present invention, the first ceramic particles and the second ceramic particles independently include at least one of aluminum oxide, boehmite, barium titanate, calcium oxide, magnesium oxide, zinc oxide, zirconium oxide, and silicon oxide.
[0094] In an embodiment of the present invention, the third binder and the fourth binder independently include at least one of polyacrylate, polybutyl acrylate, acrylonitrile-modified acrylate, and acrylamide-modified acrylate.
[0095] In an embodiment of the present invention, the first thickener and the second thickener independently include at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxyethyl cellulose, lithium carboxyethyl cellulose, sodium carboxymethyl cellulose modified with acrylate flexible chain, and lithium carboxymethyl cellulose modified with acrylate flexible chain.
[0096] In an embodiment of the present invention, the first wetting agent and the second wetting agent independently include at least one of silicone-modified polyether, silicone-modified acrylate, modified polyether acrylate, and polyol-modified acrylate.
[0097] Preferably, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell. Exemplarily, the inner layer area of the battery cell accounts for any value of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75% of the overall thickness of the battery cell, or any value within the range of any two of the above values.
[0098] In an embodiment of the present invention, the thickness of the first coating layer is 0.5-5 μm. Exemplarily, the thickness of the first coating layer is any value among 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range formed by any two of the above values.
[0099] In an embodiment of the present invention, the thickness of the second coating layer is 0.5-5 μm. Exemplarily, the thickness of the second coating layer is any value among 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range formed by any two of the above values.
[0100] In an embodiment of the present invention, the thickness of the first ceramic layer is 0.5-4 μm. Exemplarily, the thickness of the first ceramic layer is any value among 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, or any value within a range consisting of any two of the above values.
[0101] In an embodiment of the present invention, the thickness of the second ceramic layer is 0.5-4 μm. Exemplarily, the thickness of the second ceramic layer is any value among 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, or any value within the range formed by any two of the above values.
[0102] In an embodiment of the present invention, the first base film and the second base film independently include at least one of a PE base film and a PP base film.
[0103] In an embodiment of the present invention, the thickness of the first base film and the second base film are independently 4 to 20 μm. Exemplarily, the thickness of the first base film and the second base film are independently any value among 4 μm, 6 μm, 7 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm, or any value within the range formed by any two of the above values.
[0104] In the embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell. The specific embodiment of the present invention exemplifies a wound battery cell, but is not limited to a wound battery cell. A laminated battery cell can also implement the present invention.
[0105] In an embodiment of the present invention, the battery cell is a wound battery cell, the first separator and the second separator form a complete separator, the base films used for the first separator and the second separator are a continuous whole, and only the coating layer compositions of the first separator and the second separator are different.
[0106] In an embodiment of the present invention, the battery cell is a laminated battery cell, the first diaphragm includes a plurality of first sub-diaphragms, and the second diaphragm includes a plurality of second sub-diaphragms. For example, the base membranes used by the first diaphragm and the second diaphragm are two independent entities. For another example, the first diaphragm includes a plurality of first sub-diaphragms, and the base membranes of the plurality of first sub-diaphragms are a plurality of independent entities, and the second diaphragm includes a plurality of second sub-diaphragms, and the base membranes of the plurality of second sub-diaphragms are a plurality of independent entities.
[0107] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0108] In the embodiment of the present invention, the battery further includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. This application has no particular restrictions on the positive electrode sheet, the negative electrode sheet, and the electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of this application can be achieved.
[0109] In the embodiment of the present invention, the battery is a lithium ion battery, but is not limited to lithium ion batteries. Other batteries such as sodium ion batteries, potassium ion batteries, lithium sulfur batteries, zinc ion batteries, etc. can also implement the present invention.
[0110] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0111] The reagents, instruments or materials used in the present invention can be obtained through commercial channels. The binders or modified binders used in the following examples are purchased from Arkema, Sinochem Blue Sky, East Sunshine and other companies.
[0112] The present invention will be further described below in conjunction with embodiments:
[0113] Example 1
[0114] This embodiment provides a method for preparing a lithium-ion secondary battery, comprising the following steps:
[0115] (1) Preparation method of asymmetric coated diaphragm:
[0116] ① Preparation of the first ceramic layer slurry
[0117] Weigh 95.4 parts of the first ceramic particles (D 50 1.0μm alumina ceramic), 4 parts of binder (polyacrylate), 0.4 parts of thickener (sodium carboxymethyl cellulose), 0.2 parts of wetting agent (silicone modified polyether), and 285 parts of water are added into a double planetary stirring tank and mixed thoroughly to obtain the first ceramic layer slurry.
[0118] ② Preparation of the second ceramic layer slurry
[0119] 94.4 parts of second ceramic particles (0.6 μm alumina ceramics), 5 parts of binder (polyacrylate), 0.4 parts of thickener (sodium carboxymethyl cellulose), 0.2 parts of wetting agent (silicone modified polyether), and 285 parts of water were weighed and added into a double planetary stirring tank, and mixed thoroughly to obtain a second ceramic layer slurry.
[0120] ③ Preparation of the first coating slurry
[0121] 9 parts of B1 type binder (acrylic acid modified PVDF), 1 part of C type binder (acrylonitrile modified acrylate), and 90 parts of water were weighed by weight, and stirred evenly in a double planetary stirring tank to obtain a first coating layer slurry.
[0122] ④ Preparation of the second coating slurry
[0123] 9 parts of B2 type binder (hexafluoroethylene modified PVDF), 1 part of C type binder (acrylonitrile modified acrylate), and 90 parts of water were weighed by weight, and stirred evenly in a double planetary stirring tank to obtain a second coating layer slurry.
[0124] ⑤ The first ceramic layer slurry and the second ceramic layer slurry are alternately coated on the first base film and the second base film of the 7 μm PE base film, and the coating thickness is 2 μm.
[0125] ⑥ The first coating layer slurry and the second coating layer slurry are alternately sprayed on the first ceramic layer and the second ceramic layer, and the thickness of the coating layer is 3 μm.
[0126] ⑦ After drying and slicing, a diaphragm including a first diaphragm and a second diaphragm is obtained (when preparing the core, the first diaphragm is arranged in the inner layer area of the core, and the second diaphragm is arranged in the outer layer area of the core), and the structural schematic diagram is shown as follows: Figure 3 shown.
[0127] (2) Preparation of positive electrode:
[0128] 97.0 parts of positive electrode active material (lithium cobalt oxide), 1 part of conductive agent (conductive carbon black SP), 0.2 parts of dispersant (polyether modified acrylate), 1.8 parts of binder (hexafluoropropylene modified PVDF) were mixed, and an appropriate amount of N-methylpyrrolidone (NMP) was added and stirred to obtain positive electrode slurry with a solid content of 63.1%, a viscosity of 9540 mPa·s, and a fineness of 10μm. The positive electrode slurry was extruded and coated on the electrode foil, dried, rolled, and then slit and sliced to obtain the positive electrode sheet.
[0129] (3) Preparation of negative electrode sheet:
[0130] 96.5 parts of negative electrode active material (graphite), 1 part of conductive agent (conductive carbon black), 1 part of thickener (sodium carboxymethyl cellulose CMC), 1.5 parts of binder (acrylate), add deionized water to a solid content of 50% by mass, and control the viscosity to 2000 mPa·s and the fineness to 30μm to obtain a negative electrode slurry; the negative electrode slurry is extruded and coated on an electrode foil, dried, rolled, and then striped and sliced to obtain a negative electrode sheet.
[0131] (4) Battery assembly:
[0132] The positive electrode sheet, the negative electrode sheet, and the separator are wound to obtain a bare battery cell. The first separator is arranged in the inner layer area of the core, and the inner layer area of the core accounts for 50% of the overall thickness of the core. The second separator is arranged in the outer layer area of the core (such as Figure 4As shown in the figure, the first and second adhesive layers of the separator are in contact with the positive electrode sheet. Hot pressing, welding of positive and negative electrode tabs, packing of bare cells in aluminum-plastic film battery shells (or aluminum battery shells / steel battery shells / nickel-plated battery shells), liquid injection, packaging, standing, formation, and capacity division are performed to obtain a lithium-ion secondary battery.
[0133] Example 2
[0134] The only difference between this embodiment and embodiment 1 is that the type B1 binder is replaced with hydroxyl-modified PVDF.
[0135] Example 3
[0136] The only difference between this embodiment and embodiment 1 is that the type B1 binder is replaced with polycarboxylic acid-modified PVDF.
[0137] Example 4
[0138] The only difference between this embodiment and embodiment 1 is that: the D 50 The second ceramic particle D is 0.8 μm. 50 It is 0.4μm.
[0139] Example 5
[0140] The only difference between this embodiment and embodiment 1 is that: the D 50 The D of the second ceramic particle is 1.2 μm. 50 It is 0.8μm.
[0141] Example 6
[0142] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 10% of the overall thickness of the core.
[0143] Example 7
[0144] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 75% of the overall thickness of the core.
[0145] Example 8
[0146] The only difference between this embodiment and embodiment 1 is that: the D 50 The second ceramic particle D is 0.8 μm. 50 It is 0.8μm.
[0147] Comparative Example 1
[0148] The only difference between this comparative example and Example 1 is that the diaphragm in this comparative example is a conventional diaphragm. The conventional diaphragm is a 7+2+3 diaphragm (7μm PE base film + 2μm ceramic layer + 3μm rubber coating layer), wherein the formula of the ceramic layer and the rubber coating layer are respectively consistent with the formula of the second ceramic layer and the formula of the second rubber coating layer in Example 1.
[0149] Performance Testing
[0150] The performance tests of the separators and batteries of the above embodiments and comparative examples include:
[0151] (1) Climbing liquid height test:
[0152] Take a 15mm wide strip of diaphragm, place it vertically in the electrolyte, and test the electrolyte climbing height of the diaphragm. The higher the climbing height, the better the wettability of the corresponding diaphragm.
[0153] (2) Diaphragm and electrode adhesion test:
[0154] The layers consisting of the diaphragm and the positive electrode sheet in the inner layer and the outer layer of the bare battery cell obtained after hot pressing in step (4) of the embodiment and the comparative example are respectively taken to obtain the first sample and the second sample, which are cut into samples with a width of 15 cm. The diaphragm at one end is gently peeled off and vertically clamped on a tensile instrument to test the adhesion between the diaphragm and the electrode sheet at 180°.
[0155] (3) -20℃ DC internal resistance test:
[0156] At room temperature, charge the battery with 1C constant current to 3.65V, then charge it with 3.65V constant voltage to 0.05C cutoff, and then discharge it with 1C constant current to 50% SOC. Adjust the ambient temperature to -20℃, discharge it at 0.36C for 30s, and record the discharge DC internal resistance.
[0157] (4) Cycle test:
[0158] After the lithium-ion secondary battery is left to stand for 2 days at 45°C, it is first discharged at 1C to 2.0V. Then, in an environment of 25°C, a double-sided clamp with a clamp force of 3000N is used to clamp the battery. The charging process is: 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.5C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.1C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.05C; the discharge process is: standing for 5 minutes, 1C constant current discharge to 2.0V, and the discharge capacity at this time is recorded as the initial 1C discharge capacity; the charge and discharge cycle is performed in this way until the discharge capacity is 80% of the initial 1C constant current discharge to 2.0V capacity, and the number of cycles is recorded.
[0159] Table 1 Wettability of diaphragm to electrolyte and adhesion to coated diaphragm
[0160]
[0161] Note: After hot pressing the entire battery cell, the diaphragms and pole pieces in the internal and external areas are disassembled to test the adhesion. The adhesion between the first diaphragm and the pole piece is recorded as A1, and the adhesion between the second diaphragm and the pole piece is recorded as A2.
[0162] It can be seen from Table 1 that the adhesion between the diaphragm and the electrode in the inner layer of the core of Comparative Example 1 is significantly worse than that between the diaphragm and the electrode in the outer layer of the core. This is because when the battery cell is hot-pressed, the outer diaphragm is heated first and the temperature is higher. The molecular chains between the binder in the diaphragm coating layer and the PVDF in the positive electrode are more entangled with each other, and the adhesion between the corresponding diaphragm and the electrode is stronger.
[0163] The bonding strength between the first diaphragm in the inner layer area of the core and the electrode in Examples 1-8 is equivalent to the bonding strength between the second diaphragm in the outer layer area of the core and the electrode. This is because the first coating layer in the first diaphragm in the inner layer area of the core adopts polar-modified PVDF, which can improve the bonding strength with the positive electrode during hot pressing. Therefore, a better bonding effect can be obtained even when the inner temperature is low during hot pressing.
[0164] In addition, since the first ceramic layer of the first diaphragm in Examples 1-7 has added ceramic particles with larger particle sizes, the pores between the ceramics are larger, which is more conducive to the infiltration of the electrolyte. Therefore, the corresponding liquid climbing height is higher, which is beneficial to improve the wettability of the diaphragm in the inner layer area of the core with the electrolyte, thereby significantly improving the difference in wettability between the inner and outer core diaphragms.
[0165] Compared with Example 1, the particle size of the first ceramic particles and the second ceramic particles in Example 8 is the same, but the first coating layer in the first diaphragm in the inner layer area of the core uses polar-modified PVDF, which can significantly improve the adhesion. However, since the particle size of the first ceramic particles in the inner layer area of the core (0.8 μm) is slightly smaller than the particle size of the first ceramic particles in Example 1 (1.0 μm), its liquid climbing height is slightly lower than that in Example 1. However, the particle size of the second ceramic particles in the outer layer (0.8 μm) is larger than the particle size of the second ceramic particles in Example 1 (0.6 μm), and the corresponding liquid climbing height is also larger.
[0166] Table 2 DC internal resistance comparison results
[0167]
[0168] Compared with Comparative Example 1, the first separator in Examples 1-7 improves the electrolyte wettability of the inner layer area of the core, which is beneficial to reducing the internal resistance of the battery cell. The corresponding DC internal resistance at -20°C is smaller.
[0169] Compared with Comparative Example 1, the first diaphragm in Examples 1-7 improves the electrolyte wettability of the inner layer area of the core, which is beneficial to reducing the internal resistance of the battery cell, and the bonding effect between the diaphragm and the positive electrode sheet in the entire core package is similar, which is more beneficial to improving the problem of electrode misalignment during the cycle and improving the cycle performance.
[0170] In Examples 1-3, as the polar functional groups corresponding to the first binder increase, the copolymerization of the functional groups containing polar monomers will reduce the arrangement specifications of the PVDF molecular chains to a certain extent, thereby reducing the obstacles to the electrolyte entering the PVDF, and will improve the electrolyte wettability to a certain extent. The electrolyte wettability corresponding to the corresponding first diaphragm becomes better (as shown in Table 1), which is beneficial to improve the diffusion of lithium ions between particles at low temperatures, thereby helping to reduce the low-temperature DC internal resistance. In addition, it is also beneficial during hot pressing that the PVDF molecular chain mobility is enhanced, making it easier to form molecular chain interactions with the PVDF in the pole piece, and to enter the pores of the pole piece to form a mechanical anchoring effect. The corresponding first diaphragm and the pole piece have increased adhesion, which is beneficial to reducing the pole piece misalignment problem during the cycle, thereby improving the cycle performance.
[0171] The ceramic particle size of the inner area of the core in Example 4 is smaller than that of the inner area of the core in Example 1, and its corresponding electrolyte wettability is slightly worse than that in the example, but better than that in the comparative example. The ceramic particle size of the outer area of the core is smaller than that in the comparative example and Example 1, and the corresponding electrolyte wettability is worse than that in Example 1. Even if the electrolyte wettability of the outer layer of the battery cell is worse, the diaphragm in the outer layer is more easily contacted with the electrolyte and wetted. As long as the electrolyte wettability of the diaphragm in the inner layer is improved, the corresponding internal resistance of the battery cell will also be reduced to a certain extent.
[0172] In Example 5, the ceramic particle size corresponding to the inner layer area of the winding core is larger than that in Example 1, which is more conducive to electrolyte infiltration. This is because the ceramic particles are larger and the corresponding pores between the first ceramic layers are more, which is more conducive to electrolyte infiltration, thereby helping to reduce the internal resistance of the battery cell.
[0173] In Examples 6 and 7, as the thickness ratio of the first diaphragm corresponding to the first adhesive increases, the trend of reducing the DC internal resistance is more obvious, and the corresponding ability to enhance the adhesion between the diaphragm and the pole piece is increased, thereby enhancing the ability to prevent the pole piece from being dislocated, which is beneficial to improving the cycle performance.
[0174] Compared with Example 1, the particle size of the first ceramic particles and the second ceramic particles in Example 8 is the same. The first ceramic particles in the inner layer area of the winding core are smaller than those in Example 1, and the corresponding liquid creeping is worse, while the ceramic particles in the outer layer area are larger than those in Example 1, and the corresponding wettability is relatively better. Even if the electrolyte wettability of the outer layer of the battery cell is improved, the diaphragm in the outer layer is more easily contacted with the electrolyte and infiltrated, so its effect on internal resistance reduction will be relatively smaller. As a result, the overall internal resistance reduction effect is not as good as that of Example 1, but it still has certain advantages over the comparative example.
[0175] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A battery cell, characterized in that: From the center to the edge of the battery cell, it includes an inner layer area (100) of the battery cell and an outer layer area (200) of the battery cell; The inner region (100) of the battery cell refers to a region closer to the vertical central axis (300) and accounting for 10% to 75% of the overall thickness of the battery cell, and the outer region (200) of the battery cell refers to a region farther from the vertical central axis (300) and accounting for 25% to 90% of the overall thickness of the battery cell; The battery cell comprises a diaphragm (30) and a pole piece, the diaphragm (30) comprises a first diaphragm (31) and a second diaphragm (32), the first diaphragm (31) is arranged in the inner region (100) of the battery cell, and the second diaphragm (32) is arranged in the outer region (200) of the battery cell; The first diaphragm (31) comprises a first adhesive layer (313), and the first adhesive layer (313) comprises a first adhesive; The second diaphragm (32) comprises a second adhesive layer (323), and the second adhesive layer (323) comprises a second adhesive; The bonding force between the first diaphragm and the electrode piece is recorded as A1, and the bonding force between the second diaphragm and the electrode piece is recorded as A2. A1 and A2 satisfy the following relationship: -3 N / m≤A1-A2≤0 N / m; The first adhesive includes a B1 adhesive and a C adhesive, and the second adhesive includes a B2 adhesive and a C adhesive; and the mass percentage of the B1 type adhesive in the first adhesive is greater than or equal to the mass percentage of the B2 type adhesive in the second adhesive; The B1 type binder includes at least one of acrylic acid-modified PVDF, hydroxyl-modified PVDF, and polycarboxylic acid-modified PVDF; The B2 type binder includes at least one of tetrafluoroethylene modified PVDF, hexafluoroethylene modified PVDF, and trifluoroethylene modified PVDF; The type C adhesive includes at least one of acrylonitrile-modified acrylate, acrylamide-modified acrylate, acrylonitrile-modified butyl acrylate, and acrylonitrile-acrylic acid-acrylic acid terpolymer.
2. The battery cell according to claim 1, characterized in that: The bonding force between the first diaphragm and the pole piece is 7 to 10 N / m.
3. The battery cell according to claim 1, characterized in that: The bonding force between the second diaphragm and the pole piece is 9 to 11 N / m.
4. The battery cell according to claim 2, characterized in that: In parts by mass, the first binder includes: 0.1 to 20 parts of a type B1 binder and 1 to 20 parts of a type C binder; In parts by mass, the second binder includes: 0.1 to 20 parts of a B2 type binder and 1 to 20 parts of a C type binder.
5. The battery cell according to claim 1, characterized in that: The first diaphragm (31) further comprises a first ceramic layer (312), the first ceramic layer (312) being arranged between the first base film (311) and the first adhesive layer (313) of the first diaphragm (31); the second diaphragm (32) further comprises a second ceramic layer (322), the second ceramic layer (322) being arranged between the second base film (321) and the second adhesive layer (323) of the second diaphragm (32); The first ceramic layer includes first ceramic particles, the second ceramic layer includes second ceramic particles, and the particle size D of the first ceramic particles is 50 Greater than or equal to the particle size D of the second ceramic particles 50 .
6. The battery cell according to claim 5, characterized in that: The particle size D of the first ceramic particles 50 0.8~1.2μm; The particle size D of the second ceramic particles 50 It is 0.4~0.8μm.
7. The battery cell according to claim 5, characterized in that: In parts by mass, The first ceramic layer comprises: 80-98 parts of first ceramic particles, 1-20 parts of a third binder, 0.1-1 parts of a first thickener, and 0.1-1 parts of a first wetting agent; The second ceramic layer comprises: 80 to 98 parts of second ceramic particles, 1 to 20 parts of a fourth binder, 0.1 to 1 part of a second thickener, and 0.1 to 1 part of a second wetting agent.
8. The battery cell according to claim 1, characterized in that: The inner layer area of the battery core accounts for 10% to 75% of the overall thickness of the battery core.
9. The battery cell according to any one of claims 1 to 8, characterized in that: The battery core is a wound battery core or a laminated battery core.
10. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Separator, and secondary battery and electronic device comprising same
CN118369814A
Diaphragm and battery cell
CN220604899U
Lamination structure battery
JP2014026943A